STUDIES ON THE PRESERVATION OF FISH BY PICKLING - Subramanya Rao, A P; Valsan, A P; Rajendranathan Nair, M (Indian Journal of Fisheries, 2016)
Pickling with salt, vinegar, sugars and spices forms a traditional method of food preservation and is also widely employed for fish curing. A great variety of fishery products prepared with vinegar and spices enjoy wide popularity in Germany and other north European countries. Pickling is also practised in the East in countries like China, Japan and the Philippines (Jarvis, 1950). Although pickled products are of a semiperishable nature since the concentrations of salt and vinegar employed are limited by considerations of palatability, they possess a greater appeal to consumers than salted and dried fish. Moreover these methods are better suited for curing fatty fish which are susceptible to rancidity in other salting methods. Apart from a few spiced and pickled products Uke PADDA and MOLLEI prepared on a domestic scale from Seer fish, Colombo Cure of the West Coast forms the chief commercial method in India which employs principles of pickling. Mackerels, Seer and non-fatty sardines are treated by this process and Malpe in South Kanara exports considerable quantities of Colombo cured fish to Ceylon (Nicholson, 1930). Malabar tamarind or ’ Goruka PuU’, the dried fleshy pod of Garcinia cambogea is used as an adjunct to salt in order to obtain the desired acidity.